The US animal insurance program: Rapid expansion at a growing cost to taxpayers - Glauber, Joseph W. (American Enterprise Institute, 2022)
Except for dairy producers, who have benefited from price and income support programs dating back to New Deal legislation from the 1930s, coverage for livestock and livestock products remained largely confined to ad hoc supplemental disaster coverage until 2000. In 2000, livestock producers became eligible for coverage on a pilot basis under the federal crop insurance program. Unlike crop insurance, which indemnifies producers based on production or revenue losses, livestock insurance protects producers against declines in futures prices for livestock products or against declines in futures price margins between output and input products (for example, feed costs). Until 2018, coverage under livestock insurance was minimal, partly because statutory caps on expenditures limited producer subsidies. In 2018, Congress lifted the cap on expenditures, and premium subsidies were increased for livestock products. As a result, livestock insurance has grown dramatically over the past three years, with total liabilities in 2021 at $14 billion, up about 2,800 percent from just $512 million in 2018. Despite this expansion, these liabilities are still only about 10 percent of the $136 billion in total liability for all crop policies in 2021.1 Nevertheless, the recent rapid growth in participation in the federal livestock program raises concerns that the cost to taxpayers of insuring livestock may far exceed what the Congressional Budget Office (CBO) forecasted when the expenditure cap was removed from the program. Perhaps more worrying is that this program provides subsidized price support to producers who already have access to private futures and options markets that offer risk management protection against price declines. With subsidies, producers have little incentive to manage risk through private markets. Programs that guarantee minimum prices for producers are not new to agriculture, but when they are coupled to production, they can distort production and marketing decisions and harm foreign suppliers. US livestock product exports have grown significantly in recent years, and such support potentially exposes US exports to challenges by foreign suppliers through the dispute settlement mechanism at the World Trade Organization.